Impact of Bypass Fat on Growth and Testicular Measurements in Gaddi Goat Bucks - Sambyal, Madhu Suman; Shivani Katoch; Nishant Verma; Devesh Thakur; Krishanender Dinesh (Indian Journal of Animal Nutrition, 2025)
The present study was conducted with the objective to compare the morphometric, antioxidative and immunity parameters of Gaddi goat kids fed rumen protected fat and control group for 120 days. Twenty two Gaddi male goat kids (6-8 months) were selected from the flock and divided into two groups (11 kids each) in a completely randomized design. The kids were taken for grazing in the day time and offered concentrate mixture in the evening fortified with bypass fat @ 5% of dry matter. The overall average daily body weight gain was higher (P≤0.05) in treatment group as compared to control. The overall average scrotal circumference and scrotal volume, of Gaddi bucks in control and treatment group were significantly more (P≤0.05) in treatment group as compared to control. The average length of the right and left testis in treatment group was more and in right testes it was significantly (P≤0.05) higher on IIIrd and IVth month of treatment. Similarly overall average width of the right and left testis in treatment group was more as compared to control. Superoxide dismutase (SOD) catalase activities and total immunoglobulin (mg/ml) values not affected by treatment, however, at the end of the experimental feeding, there was a significant (P≤0.05) increased in FRAP value in treatment group than in control. Results of the present study indicate that feeding of bypass fat can be useful strategy for the improvement of growth performance, morphometric parameters and antioxidative status in Gaddi bucks.